Gains and losses of India-China trade cooperation: a gravity model impact analysis - Swapan K. Bhattacharya; Biswa N. Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2007)
As revealed by the trade intensity indices, India and the People's Republic of China have significant bilateral trade potential, which remains unexplored until now. These countries are presently negotiating for free trade arrangements among them based on their complementarities. This paper makes an attempt to estimate the likely benefits in terms of gains or losses in imports of both India and China due to different preferential trading arrangements and free trade arrangements using the gravity model. Empirical results show that in the short run India's potential gain is relatively less compared to China because of its high tariffs but in the long run, India's gains are higher than China once its tariff levels are brought at par with them. Free trade arrangement is a win-win situation for both countries and is consistent with their growing dominance in the international trade.
Keywords: F02; F04; F13; F14; F15; 330; Freihandel; Internationale Wirtschaftsbeziehungen; Außenhandelseffekt; Kosten-Nutzen-Analyse; Gravitationsmodell; Indien; China